Medidas de segurança no Brasil : o exercício do poder (penal) no âmbito da normalização terapêutica - Castelo Branco, Thayara Silva (2016)
This is a study that aims to analyze the permanence of the security measures in the criminal Brazilian law. The construction of the pedagogy of the order and control is analyzed from the racist-hygienic-disciplinary paradigm that embodied the social medicine as the new health policy model from the second half of the nineteenth century, until the emergence of the social therapeutic control, built on hospital (psychiatric) grounds. In this context, the new relationship between medicine and the state is developed, through the instruction of the medical police. The founding of the Nina Rodrigues School and its contributions to the medical-legal context are discussed. The medical debate on the Bahia Medical Gazette publications is then presented, which in the late nineteenth century had the importance of setting medical science as scientific knowledge capable of solving the socio-political problems of the country. As opposed to the medical discourse, there is the Law School of Recife and its subsidies for a new legal criminal design, seeking to demonstrate which of the sciences was more able to save Brazil. Next, the criminal-psychiatric symbolism reflected in the legislative process since the late nineteenth century until the reform of 1984 is presented, as well as the construction of custody and psychiatric treatment hospitals and the statistics that show a current overview on the implementation of the security measures. Considering such structures, the grounds of the anti-psychiatric movement, from the Italian reform movement led by Franco Basaglia and, ultimately, its influences on the Brazilian Psychiatric Reform. Finally, the process of (de)legitimation of the security measures in Brazil is shown, with its justifications, alternative models to the prison-asylum system and the issues that lead to the hypothesis of the in(viability) to overcome the criminal-psychiatric model.